Las ciencias ambientales interdisciplinarias del presente y futuro: ecología aplicada, biología integrativa y ecología integral - Illescas Cobos, Abiael Alexis (Pontificia Universidad Católica del Perú, 2025)
This essay analyzes the interrelation between applied ecology, integrative biology, and integral ecology as key disciplines in environmental sciences. It examines their interdisciplinary foundations, similarities, and differences from a reflective perspective, highlighting how their prospects and potential integration can contribute to addressing contemporary environmental challenges. Applied ecology focuses on the practical resolution of environmental problems. Integrative biology delves into the interactions among organisms, their evolution, and their environment. Integral ecology provides a framework to address the interconnections between natural and sociocultural systems. Based on a strategic selection of literature, this essay analyzes these disciplines in their respective contexts to underscore their relevance in research aimed at developing sustainable and holistic solutions to current and future environmental challenges.

Este ensayo analiza la interrelación entre ecología aplicada, biología integrativa y ecología integral como disciplinas clave en las ciencias ambientales. Examina desde una perspectiva reflexiva sus fundamentos interdisciplinarios, similitudes y diferencias, destacando cómo sus prospectivas, y una posible integración, pueden contribuir a enfrentar los retos ambientales contemporáneos. La ecología aplicada se enfoca en la solución práctica de problemas ambientales. La biología integrativa profundiza en las interacciones entre organismos, su evolución y entorno. La ecología integral ofrece un marco para abordar las interconexiones entre sistemas naturales y socioculturales. Basado en una selección estratégica de literatura, este ensayo analiza estas disciplinas en sus respectivos contextos para destacar su relevancia en investigaciones dirigidas al desarrollo de soluciones sostenibles y holísticas frente a los desafíos ambientales actuales y futuros.
Interdisciplinary environmental sciences of the present and future: applied ecology, integrative biology, and integral ecology
Keywords: Interdisciplinarity; Sustainability; Ecological complexity; Problem-solving; Holistic perspective; Interdisciplinariedad; Sostenibilidad; Complejidad ecológica; Resolución de problemas; Visión holística; https://purl.org/pe-repo/ocde/ford#2.07.01